1985
DOI: 10.1111/j.1469-7610.1985.tb02260.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Autistic Children

Abstract: The goals of treatment need to be decided on the basis of knowledge on the nature of autism. As with any developmental disorder, the first goal must be to foster normal development; with autistic children this involves a focus on intellectual, language and social development. The further goals include: the reduction of rigidity/stereotypy; the elimination of non-specific maladaptive behaviours; and alleviation of family distress. Research findings are used to translate these goals into a practical overall ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 45 publications
0
43
0
6
Order By: Relevance
“…As stated by Fenichel (1976), "disorganized children need someone to organize their world for them……training that can bring order, stability and direction to minds that are disorganized, unstable and unpredictable" (p.220). Rutter (1985) supported this position and further suggested that psychosocial programs to remediate the social deficits of children with ASD should provide planned periods of structured social interaction. It is possible that the structured physical environment, visual support, steady and slowly switching, and notice about transitions in advance made the play context predictable and comprehensible, and therefore, the treatment did not stimuli their negative behaviors and autistic features.…”
Section: Discussionmentioning
confidence: 78%
“…As stated by Fenichel (1976), "disorganized children need someone to organize their world for them……training that can bring order, stability and direction to minds that are disorganized, unstable and unpredictable" (p.220). Rutter (1985) supported this position and further suggested that psychosocial programs to remediate the social deficits of children with ASD should provide planned periods of structured social interaction. It is possible that the structured physical environment, visual support, steady and slowly switching, and notice about transitions in advance made the play context predictable and comprehensible, and therefore, the treatment did not stimuli their negative behaviors and autistic features.…”
Section: Discussionmentioning
confidence: 78%
“…The focus on biomedical causes (i.e., genetic, neurological) lead naturally to a search for medical treatments. In contrast, the focus on abnormalities in behavioral, emotional, and cognitive development lead to an emphasis on psychological or behavioral interventions [Rutter, 1985]. However, although both theoretical approaches make claims with respect to putative etiological and pathophysiologic factors, the pathogenesis of autism has remained largely unknown.…”
Section: Empirically Validated Treatments For Autismmentioning
confidence: 93%
“…In autism, this core area is characterized by a variety of overt behavioral symptoms, including stereotyped motor behaviors (e.g., hand-flapping, body-rocking, object spinning), rituals and routines (e.g., ordering items or events, insisting on sameness), obsessional restricted interests (e.g., nonfunctional consuming interest in train schedules), and also a more general characteristic of rigidity/inflexibility and poor response to novelty [Rutter, 1985;Lewis and Bodfish 1999;Bodfish et al, 2000]. To date, the treatment of the repetitive behavior core features of autism has received far less study than the treatment of the social and communication deficits of autism.…”
Section: Repetitive Behavior Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parmi ceux qui acquiè-rent un langage, tous présentent des anomalies majeures du développe-ment de la parole telles l'écholalie immédiate ou retardée (APA, 1994), l'inversion des pronoms personnels (Rutter, 1978(Rutter, ,1985, des difficultés à utiliser des termes abstraits et à utiliser un langage métaphorique.…”
Section: Les Altérations Qualitatives De La Communication Et De L'actunclassified